2020
DOI: 10.3390/cryst10080707
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Blast-Resistant Performance of Steel and PVA Fiber-Reinforced Concrete: Experimental and Numerical Analyses

Abstract: This paper deals with the blast-resistant performance of steel fiber-reinforced concrete (SFRC) and polyvinyl alcohol (PVA) fiber-reinforced concrete (PVA-FRC) panels with a contact detonation test both experimentally and numerically. With 2% fiber volumetric content, SFRC and PVA-FRC specimens were prepared and comparatively tested in comparison with plain concrete (PC). SFRC was found to exhibit better blast-resistant performance than PVA-FRC. The dynamic mechanical responses of FRC panels were numerically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Afroughsabet et al [ 39 ] found that, with the incorporation of polyvinyl alcohol fibers, the dry shrinkage of concrete during precuring significantly decreased. Chen et al [ 40 ] found that the incorporation of polyvinyl alcohol fibers significantly enhanced the blast resistance of concrete. Zhao et al [ 41 ] placed polyvinyl-alcohol-fiber concrete in a freeze–thaw environment and subjected samples to a sulfate attack in a seawater environment.…”
Section: Introductionmentioning
confidence: 99%
“…Afroughsabet et al [ 39 ] found that, with the incorporation of polyvinyl alcohol fibers, the dry shrinkage of concrete during precuring significantly decreased. Chen et al [ 40 ] found that the incorporation of polyvinyl alcohol fibers significantly enhanced the blast resistance of concrete. Zhao et al [ 41 ] placed polyvinyl-alcohol-fiber concrete in a freeze–thaw environment and subjected samples to a sulfate attack in a seawater environment.…”
Section: Introductionmentioning
confidence: 99%
“…As an important material for infrastructure construction and civil engineering, the cementitious composite exhibits high compressive strength but low tensile strength and poor impact resistance. 1,2 Ultra-highperformance cementitious material has a higher strength, but still features obvious brittleness. 3 In order to improve the mechanical properties of cementitious material, steel fibers 4,5 are used as reinforcements, but they are easily corroded, 6 which will shorten the service life of the concrete.…”
mentioning
confidence: 99%
“…As an important material for infrastructure construction and civil engineering, the cementitious composite exhibits high compressive strength but low tensile strength and poor impact resistance. 1,2 Ultra-high-performance cementitious material has a higher strength, but still features obvious brittleness. 3…”
mentioning
confidence: 99%
“…Phutthimethakul et al [18] used flue gas desulfurization gypsum, construction and demolition waste, and oil palm waste trunks to produce concrete bricks. Chen et al [19] experimentally and numerically studied the blast-resistant performance of steel fiber-reinforced concrete and polyvinyl alcohol fiber-reinforced concrete panels with a contact detonation test.…”
mentioning
confidence: 99%